Sistem Informasi Pendistribusian Suku Cadang Industri pada CV. Oilfindo Menggunakan Metode Rational Unified Process - Effendi, Hendra; Beny, Beny (Sekolah Tinggi Manajemen Informatika dan Komputer PalComTech, 2019)
CV. Oilfindo is a company engaged in the supply of oil and gas industry spare parts. CV. Oilfindo works routinely in carrying out mutually supportive assignments in the delivery of spare parts to several consumers in several cities. Based on the interview, the constraints that are found are on time efficiency and slow employee performance. The purpose of conducting this research is to create an Industrial Parts Distribution Information System on the CV. Oilfindo Using Rational Unified Process Method. The methodology used in system development is Rational Unified Process (RUP) methodology which includes 4 stages of work, namely the inception phase, the elaboration phase, the construction phase, and the transition phase. In designing the system, 3 diagrams are used, namely class diagrams, use case and activity diagrams. The results of the application of the Information System The distribution of industrial parts is expected to help employees in facilitating the process of distribution to consumers. Keywords—Information Systems, Distribution, Parts, RUP, Code Igniter